دور الصناديق الوقفية في مكافحة الجريمة لتحقيق الاستقرار الأمني إمارة دبي نموذجا : دراسة تحليلية - يوسف، آمنة محمد حسن (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
The research aims to highlight the application of a proposed waqf (endowment) model in the Emirate of Dubai to address crime and reduce its effects, especially the crime of drugs, whether on the person who is punished for the crime, or his family who may be harmed for his or her ill-will, or the victims who have committed the crime. On the other hand, it deals with the development of charitable waqf which aimed at containing the causes and motives of the crime before it occurs through a conscious study of the characteristics of society, the knowledge of the vulnerable groups in it and the risk of committing the crime under social, economic or other circumstances, and thus to neutralize or address them, as well as the consequences of the existence of a fund, waqf and ways of developing it, then a set of solutions that could contribute to supporting and continuing the fund to play its role in the fight against crime. The researcher followed a set of research methodologies that addressed the study through the historical approach. The researcher listed the history of the waqf in the various Islamic times, and the history of the waqf in The Emirate of Dubai in particular, by employing the comparative method in comparing between the waqf funds in Kuwait. It was also using the inductive approach to identify the views of those concerned and scholars in the creation of the waqf model. The researcher also used the analytical method in order to reach the results that had to address the research problem by analyzing the figures for the study sample. The study concluded a series of findings, the most important of which is the need to establish a sustainability-based model and standby model to reduce the negative effects or repercussions of crime, including drug crime. The researcher also concluded her study with a set of recommendations, the most important of which is the issuance of legal legislation from the relevant authorities begin the establishment of the proposed endowment fund model.